DESIGNING A GAME-INSPIRED CLASSROOM: VIDEOGAMES AS MODELS OF GOOD TEACHING - Holmes, Jeffrey Brandon (AoIR Selected Papers of Internet Research, 2015)
This paper describes the design of a “game-inspired” undergraduate course based on the premise that games demonstrate good teaching methods, not just good learning contexts. It uses games as an inspiration for designing instructional experiences in which learners can realize the various principles Gee (2003) first described without necessarily creating game-like experiences. Instead, this game-inspired teaching is a way of recognizing the effective pedagogical methods videogames use as part of the “good learning tools” Gee has described tied to what we know about learning and teaching, particularly as described by Hattie and Yates (2013). Indeed, it is possible to reconsider Gee’s learning principles as design principles which can drive instructional practice. These design features allow teachers to structure learning experiences in ways that work for their particular learning goals and leverage the growing body of game-based learning research (Tobias and Fletcher, 2011). These design principles also allow for flexibility in creating a course or other learning environment by serving as guidelines and not absolutes; the type of content, the type of learner, and the various affordances and limitations of the teaching spaces change the ways in which game- inspired teaching methods might be useful, so teachers may use them as guidelines rather than being stuck within rigid boundaries of game scenarios.